The Effectiveness Of Parents’ Role In The Prevention Of Stunting Toddlers In Highlands Of Bengkulu - Haryani, Sri; Bakara, Derison Marsinova; Buana, Chandra (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2022)
Stunting or short stature is a condition of failure to develop in babies (0-11 months) and toddlers (12-59 months) due to chronic malnutrition, especially in the first 1,000 days of life so they are too short for their age. Malnutrition occurs since the baby is in the womb and in the early days after the baby is born, but stunting conditions only appear after they are 2 years old. Stunting is a chronic condition that describes stunted growth due to malnutrition in the long term. In 2019, 15.0% of toddlers in the world are stunted. This study aimed to determine what factors cause stunting in toddlers in the highlands of Bengkulu in 2020. This study used an analytical observational with a cross-sectional research design. The results of the multivariate test in this study obtained a value of p < 0.05, where toddlers’ birth weight (p = 0.153), maternal age (p = 0.206), parental occupation (p = 0.079), maternal educational background (p = 0.079), parental income (p = 0.032), exclusive breastfeeding (p = 0.852), and maternal employment status (p = 0.079). From these results, it is found that there is no significant relationship between toddlers’ birth weight, maternal age, parental occupation, maternal educational background, exclusive breastfeeding, and maternal employment status and stunting incidence in the highlands of Bengkulu in 2020. Meanwhile, there is a relationship between parental income and stunting incidence in the highlands of Bengkulu in 2020.